2011
DOI: 10.1002/jez.713
|View full text |Cite
|
Sign up to set email alerts
|

Defence against oxidative stress in two species of land snails (Helix pomatia and Helix aspersa) subjected to estivation

Abstract: During summer, land snails are exposed to estivation/arousal cycles that imposes oxidative stress, but they exhibit different patterns of antioxidant defence. To test the ability of two related species, Helix pomatia and Helix aspersa, to modulate their antioxidant defence mechanism during estivation/arousal cycles, we examined activities of catalase and glutathione-related enzymes and concentrations of glutathione and thiobarbituric acid reactive substances (TBARS; as products of lipid peroxidation). In both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…The kidney and the foot had generally lower TBARS levels, but both showed increased damage during estivation, and a recovery at 24h of arousal, which indicates here the operation of effective antioxidant defences during arousal. Comparisons of TBARS levels between organs in both the freshwater P. canaliculata as well as in the terrestrial gastropods Otala lactea (Hermes-Lima and Storey, 1995), Helix aspersa (Ramos-Vasconcelos and Hermes-Lima, 2003) and Helix pomatia (Nowakowska et al, 2011) showed lower values in the foot than in the midgut gland. Also, Nowakowska et al (Nowakowska et al, 2011) found even lower levels in the kidney than in the foot of H. aspersa.…”
Section: Antioxidant Protectionmentioning
confidence: 95%
See 4 more Smart Citations
“…The kidney and the foot had generally lower TBARS levels, but both showed increased damage during estivation, and a recovery at 24h of arousal, which indicates here the operation of effective antioxidant defences during arousal. Comparisons of TBARS levels between organs in both the freshwater P. canaliculata as well as in the terrestrial gastropods Otala lactea (Hermes-Lima and Storey, 1995), Helix aspersa (Ramos-Vasconcelos and Hermes-Lima, 2003) and Helix pomatia (Nowakowska et al, 2011) showed lower values in the foot than in the midgut gland. Also, Nowakowska et al (Nowakowska et al, 2011) found even lower levels in the kidney than in the foot of H. aspersa.…”
Section: Antioxidant Protectionmentioning
confidence: 95%
“…Hence the high concentrations of glutathione observed before the hypometabolic situation and the recovery of the control levels after it, fit GSH changes into the first of the proposed strategies (Storey, 1996). Oxidation of GSH is a phylogenetically spread and efficient mechanism of antioxidant defense that is important in terrestrial gastropods, both during and after hypometabolic situations (Hermes-Lima and Storey, 1995;Ramos-Vasconcelos et al, 2005;Nowakowska et al, 2009;Nowakowska et al, 2011). In the latter gastropods, as well as in P. canaliculata, GSH concentration was higher in the midgut gland than in the foot (Hermes-Lima and Storey, 1995;Ramos-Vasconcelos and Hermes-Lima, 2003;Nowakowska et al, 2009) (Fig.1D), and the sustained levels observed during the activity-estivation cycle indicate that GSH is an effective antioxidant defence mechanism in the midgut gland, avoiding the elevation of TBARS levels in the cycle.…”
Section: Defences During Estivation and Arousalmentioning
confidence: 99%
See 3 more Smart Citations